"You are not alone": A big data and qualitative analysis of men's unintended fatherhood - Imogene Smith; George J. Youssef; Adrian Shatte; Samantha J. Teague; Tess Knight; Jacqui A. Macdonald (Elsevier, 2022)
Background: Becoming a father is a profound change in a man's life that is not always planned or wanted. Little is known about the subjective experiences of men who become fathers unintentionally or reluctantly. The aim of this research was to explore how men who did not intend to have children discuss their feelings about becoming a father in an online, anonymous environment. We sought insights into emotional responses, appraisals of family functioning, and relationships with infants. Method: Data were collected from two Reddit forums for new and expectant fathers, r/Daddit and r/Predaddit. Approximately 2600 posts and 21,000 comments were extracted from the period between January 2019 and March 2020. We employed a two-stage methodology, blending big data techniques and qualitative analyses. Stage One included extraction and data preparation for topic modelling Stage Two was an adapted approach to thematic qualitative analysis. Results: Topic modelling revealed 49 topics of which 6 were relevant thematically to unintended fatherhood. Men's communication in these were then classified within three domains: 1) Men's Concerns included their mental health, problems bonding with baby, their relationships with family and partner, and finances; 2) Men's Affective Experiences existed on a spectrum of complex emotions including regret, resignation, ambivalence, acceptance, and excitement; and 3) the Purpose of Communication included asking for and offering advice, normalisation, and perspective. Conclusions: Online forums like Reddit provide a unique opportunity for fathers who did not intend to have children to normalize their experience by expressing concerns and emotions in a pseudonymous environment. This study highlights the supportive environment that online discussions offer to fathers, and particularly unexpected fathers who may face stigma or barriers in other settings.